Changes in health-related outcomes among colorectal cancer patients undergoing inpatient rehabilitation therapy: a systematic review of observational and interventional studies - Scherer-Trame, Sophie; Jansen, Lina; Boakye, Daniel; Hoffmeister, Michael; Brenner, Hermann (Acta oncologica, 2021)
Colorectal cancer (CRC) and its treatment can lead to several physical and psychosocial impairments. Cancer rehabilitation aims to reduce morbidity and improve quality of life. The objective of this review was to summarize and evaluate evidence on changes in health-related outcomes among CRC patients undergoing inpatient rehabilitation therapy and on the effectiveness of such treatment. We conducted a systematic literature search including the electronic databases Pubmed and Web of Science to find observational and interventional studies, which investigated changes in health-related outcomes among CRC patients undergoing multidisciplinary inpatient rehabilitation programs or treatment effects. Study findings were synthesized narratively. Eleven studies were eligible and included in this review. Eight patient cohort studies addressed outcomes such as physical and functional status, fecal incontinence, anxiety and depression, and quality of life. Positive changes during rehabilitation therapy were observed for physical health (functional and physical status, fecal incontinence), and several dimensions of quality of life. Study findings concerning anxiety and depression were not conclusive. Studies that additionally conducted long-term follow-ups indicated that the improved health status after rehabilitative treatment waned over time. One RCT reported no effect of inpatient rehabilitation on distress and two randomized trials reported effects of exercise intensity on oxidative stress and immune response. Sample sizes were low (<100 included CRC patients) in eight studies and only the RCT included a comparison group (non-rehabilitants). The scientific evidence level was very limited. Due to the lack of a comparison group in most studies, we were only able to evaluate changes during/after inpatient rehabilitation therapy but not the effectiveness of treatment. However, study findings suggest that physical health and functional independence improve during inpatient rehabilitation, but improvements wane over time. Further large representative studies, in particular RCTs with long-term follow-up, are essential to evaluate the effectiveness of inpatient rehabilitation and identify determinants of treatment success.
"Published online: 19 Oct 2020".- Artikelübersicht
Gesehen am 05.09.2024